THE PORTRAYAL OF WOMEN IN CHARLOTTE BRONTË'S "JANE EYRE" AND JANE AUSTEN'S "PRIDE AND PREJUDICE" - Sevara Usmonova Sultanovna; Tojidinova Diyora (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract Multiple marriage proposals in Jane Austen's Pride and Prejudice and Charlotte Brontë's Jane Eyre are the focus of this article. I'll demonstrate how the narrative structures of Austen's and Brontë's works are fundamentally shaped by the inclusion of two proposals, one from Darcy and the other from Rochester. In order to illustrate when a proposal should be accepted, I will look at how Austen and Brontë present their heroines with multiple proposals. Through discussions with a number of literary experts who study Austen and Brontë, this thesis will place Elizabeth Bennet and Jane Eyre's decisions in context. The first chapter will analyze Darcy and Elizabeth's evolving relationship and discuss Jane Austen's Pride and Prejudice. The second chapter will look at Jane Eyre by Charlotte Brontë and how her personal journey connects to her relationship with Rochester. I'll also look at how each author illustrates how gender norms and stereotypes can be detrimental to both one's personal growth and the stability of a relationship.